ORGANIZATIONAL CULTURE AS A KEY FACTOR FOR SKILLS DEVELOPMENT IN THE NON-GOVERNMENTAL SECTOR - Bakardzhieva, Krasimira (E-Journal VFU, 2025)
The aim of the study is to analyze the correlations between organisational culture and skills development in the non-governmental sector. Vies on the key competences are examine as a lifelong development strategy. The article presents part of the results of an empirical study of 285 respondents regarding the correlation between organisational culture and skills development in the non-governmental sector. It is based on the concept established qualification frameworks and strategies for organisational development.
Keywords: lifelong learning; skills; competences; non-governmental sector